Feeding Glycyrrhiza glabra (liquorice) and Astragalus membranaceus (AM) alters innate immune and physiological responses in yellow perch (Perca flavescens). (July 2016) - Elabd, Hiam; Wang, Han-Ping; Shaheen, Adel; Yao, Hong; Abbass, Amany
Abstract: The current work assessed the potential immunomodulatory and growth-promoting effects of Astragalus membranaceus (AM) and Glycyrrhiza glabra (liquorice) in Yellow perch ( Perca flavescens ). In this regard, fish with an average weight of 31 ± 1.0 g were divided into five groups, and fed daily with an additive-free basal diet (control); 1, 2, and 3% (w/w) Glycyrrhiza glabra, and the fifth diet was incorporated with a combination of 1% G. glabra -AM for a four-week period. Immunological, biochemical and growth parameters were measured; and sub-groups of fish were exposed to 1-week starvation. The results showed that incorporating AM and liquorice in the diet significantly improved Immunological [superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), Lipid peroxidase (LPx) and lysozyme activities], biochemical [Aspartate Aminotransferase (AST) and Alanine Transaminase (ALT) activities; and glucose and cortisol concentrations] and growth performance parameters [body mass gain (BMG), specific growth rate (SGR), length, condition factor (K) and feed conversion ratio (FCR)]. In addition, markedly up-regulated the expression of related genes [Insulin-Like Growth Factor-1 (IGF-1), Serum amyloid A (SAA), Complement Component C3 (CCC3), Alpha 2 Macroglobulin (A2M), SOD and GPx] in treated fish groups compared to the control. Conclusively, feeding AM and liquorice diets significantly increased (P < 0.05) growth performance, antioxidant and immune response profiles throughout the entire experiment, suggesting their beneficial rule as natural anti-stress agents. Highlights: Astragalus membranaceus and Glycyrrhiza glabra improve innate immune response of yellow perch. Astragalus membranaceus and Glycyrrhiza glabra alter physiological responses in yellow perch. Astragalus membranaceus and Glycyrrhiza glabra can be used as natural anti-stress agents in aquaculture.